Analysis of Grit on the Implementation of the Pancasila Student Profile - Rohmah, Afifatur; Ainy Fardana, Nur; Hery Yunanto, Nono (CV. Publikasi Indonesia, 2025)
The development of high-quality and character-driven human resources is a national priority program. Human resources in Indonesia must be based on Pancasila values. Therefore, the Ministry of Education, Culture, Research, and Technology is committed to realizing the Pancasila Student Profile. Educators play a key role in implementing the Pancasila Student Profile. This research aims to gain deeper insight into the implementation of the Pancasila Student Profile through the concept of grit, which is identified as a form of educator resilience in facing students’ moral degradation. This research uses a qualitative method. The method used is a qualitative approach with a phenomenological design. The data was obtained through in-depth interviews with two respondents who were teachers and elementary school principals. The results showed that both respondents had a high level of grit, characterized by strong motivation, consistency in facing challenges, and resilience in the face of psychological pressure from parents and the environment. Educators can incorporate Pancasila values into the learning process despite post-pandemic challenges. The conclusion of this study states that grit is an important factor in the successful implementation of the Pancasila Student Profile. The implications of this study highlight the importance of strengthening the capacity and psychological resilience of teachers in implementing national character programs. Further research is suggested to include more respondents and adopt a multi-level approach to examine the influence of cross-school and institutional policies on the implementation of character values.